2021
DOI: 10.12998/wjcc.v9.i13.3200
|View full text |Cite
|
Sign up to set email alerts
|

Alström syndrome with a novel mutation of ALMS1 and Graves’ hyperthyroidism: A case report and review of the literature

Abstract: BACKGROUND Alström syndrome (AS, OMIM ID 203800) is a rare disease involving multiple organs in children and is mostly reported in non-Chinese patients. In the Chinese population, there are few reports on the clinical manifestations and pathogenesis of AS. This is the first report on the association between AS and Graves’ hyperthyroidism. CASE SUMMARY An 8-year-old Chinese girl was diagnosed with AS. Two years later, Graves’ hyperthyroidism developed with progressive li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Finally, the ALMS1 sequence has already described the presence of a lncRNA, ALMS1-IT1, with a role in regulating proliferation in various types of cancers and neuroinflammation and a pseudo gene, ALMS1P1, whose function is still unknown (Lu et al, 2021;Luan et al, 2021;Mei et al, 2021). Due to the large length of the ALMS1 gene, the presence of more of these elements would not be uncommon and could explain why the localisation of the cLOF variant can lead to different phenotypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the ALMS1 sequence has already described the presence of a lncRNA, ALMS1-IT1, with a role in regulating proliferation in various types of cancers and neuroinflammation and a pseudo gene, ALMS1P1, whose function is still unknown (Lu et al, 2021;Luan et al, 2021;Mei et al, 2021). Due to the large length of the ALMS1 gene, the presence of more of these elements would not be uncommon and could explain why the localisation of the cLOF variant can lead to different phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…After a thorough reading of the article, the study was included if the following characteristics were met: the cohort of the article included a patient with a diagnosis of ALMS, and the diagnosis had a genetic and clinical characterisation. Articles whose diagnosis of ALMS was based solely on phenotype were discarded, (Charles et al, 1990;Holder et al, 1995;Russell-Eggitt et al, 1998;Koray et al, 2001;Worthley and Zeitz, 2001;Benso et al, 2002;Satman et al, 2002;Paisey et al, 2004;Hoffman et al, 2005;Hamamy et al, 2006;Koç et al, 2006;Gogi et al, 2007;Silan et al, 2013;Bronson et al, 2015;Boerwinkle et al, 2017;Davies et al, 2018) , as well as those that simply presented or reported the patient's mutations without giving an complete (Lazar et al, 2015) or individualised clinical history (Patel et al, 2006;Marshall et al, 2007bMarshall et al, , 2015Redin et al, 2012;Kilpinen et al, 2017;Gao et al, 2019;Baig et al, Bea-Mascato et al, 2021;Saadah et al, 2021;Srikrupa et al, 2021;Zhang et al, 2021) were selected for information extraction and subsequent analyses.…”
Section: Study Selectionmentioning
confidence: 99%